Long-term follow-up of the red density pilot trial: a basis for long-term prediction of sustained clinical remission in ulcerative colitis? - Sinonquel, Pieter; Bossuyt, Peter; Sabino, João Pedro Guedelha; Verstockt, Bram; Makino, Takao; Vermeire, Severine; Bisschops, Raf (Endoscopy International Open, 2023)
Red density (RD) technology is an automated operator-independent endoscopic scoring system for disease activity in ulcerative colitis (UC). In this retrospective analysis we aimed to assess the predictive value of the RD sore for sustained clinical remission. All 39 patients from the RD pilot trial were evaluated for clinical outcome in a 5-year period. The highest RD score was considered for Receiver operating characteristic (ROC) analysis to determine the cut-off of the RD for the composite endpoint of treatment failure (defined as mortality, colectomy, hospitalizations, flares and UC therapy changes). Statistical significance was considered P < 0.05. Reassessment of the RD score was possible in 36 patients. The composite endpoint was reached in 17 of 39 patients. ROC analysis for clinical remission showed a RD cut-off of 65, area under the ROC was 0.68, sensitivity of 0.71, and a specificity of 0.63. A RD score of ≥ 65 demonstrated a statistically non-significant increase in composite endpoint (hazard ratio 0.49 (95% confidence interval 0.1871-1.280); P = 0.1453). In conclusion, the RD score may be an independent predictor of clinical remission in patients with UC for the disease course up to 5 years, but results of the ongoing PROCEED-UC trial are to awaited for definite conclusions.
Keywords: Endoscopy Upper GI Tract; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE); Endoscopy Lower GI Tract; Inflammatory bowel disease; Quality and logistical aspects; Quality management